In-situ electrochemical reconstruction of rock-salt phase natio2 and its application in sodium-ion capacitors

CN122889600APending Publication Date: 2026-10-09LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611014512.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]针对现有钠离子电容器负极材料钠离子脱嵌动力学迟缓、体积膨胀严重、结构稳定性差,以及正负极动力学匹配性差、综合性能受限的不足,本发明目的是在于提供岩盐相NaTiO2的原位电化学重构方法及其在钠离子电容器中的应用,通过原位电化学重构策略实现锐钛矿相TiO2向高稳定性岩盐相NaTiO2的原位相变,优化钠离子传输通道,缓解电极体积形变,同时搭配多孔碳正极与适配电解液体系,实现正负极动力学精准匹配,协同提升钠离子电容器的能量密度、功率密度与循环稳定性

Benefits of technology

1、本发明通过原位电化学重构策略实现锐钛矿相TiO2向岩盐相NaTiO2的可控相变,优化电极微观结构,大幅提升钠离子传输速率,解决了传统钛基负极钠离子脱嵌动力学迟缓、体积膨胀严重、结构稳定性差的行业痛点,电极倍率性能与结构稳定性显著提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889600A_ABST
    Figure CN122889600A_ABST
Patent Text Reader

Abstract

The application discloses an in-situ electrochemical reconstruction method of a rock salt phase NaTiO2 and application of the rock salt phase NaTiO2 in a sodium ion capacitor, uses an anatase TiO2 nanomaterial as a precursor, prepares a TiO2 electrode and assembles a sodium metal half-battery, then realizes in-situ crystal phase reconstruction through electrochemical activation such as cyclic voltammetry or constant current charging and discharging, and irreversibly converts the anatase TiO2 electrode into a cubic rock salt phase NaTiO2 negative electrode with continuous octahedral ion channels; meanwhile, the sodium ion capacitor is assembled by matching a capacitive porous carbon positive electrode and a wide potential window sodium salt electrolyte. The rock salt phase NaTiO2 generated in-situ has stable crystal structure, excellent sodium ion diffusion dynamics and strong volume change buffering capacity in a cycle process; the constructed sodium ion capacitor realizes kinetic matching of the battery type negative electrode and the capacitive positive electrode, and has an ultra-long cycle life. The raw material is easy to obtain, the preparation process is compatible with an existing electrode production line, the cost is low, and the application can be scaled up in a power grid energy storage and industrial standby power supply scene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, specifically to a high-rate performance rock salt phase NaTiO2 anode material prepared by an in-situ electrochemical reconstruction method, and a high-performance sodium-ion capacitor constructed based on the NaTiO2 anode material. Background Technology

[0002] Against the backdrop of the accelerated construction and steady advancement of new power systems, the iterative upgrades of energy storage technology are driving electrochemical energy storage systems toward the synergistic goal of higher energy density and higher power density. This places increasingly stringent standards on the comprehensive service performance of high-performance electrochemical energy storage devices, requiring not only higher energy density for long-term energy storage, but also excellent power density to meet the demands of instantaneous high-power charging and discharging, while also ensuring ultra-long cycle life, good safety, and low manufacturing costs.

[0003] Under this trend, sodium-ion capacitors, which combine the advantages of both energy storage and energy storage, have emerged as a leading technology. This device perfectly integrates the core characteristics of sodium-ion batteries—high energy density and ample storage capacity—while inheriting the outstanding advantages of supercapacitors—fast charging and discharging, strong power output, and sensitive response. Furthermore, sodium-ion capacitors are widely applicable to various scenarios such as grid energy storage, automotive energy storage, and industrial backup power, overcoming the performance deficiencies of traditional energy storage devices. They represent a novel, highly efficient electrochemical energy storage technology with significant research value and potential for large-scale application.

[0004] Despite these advantages, existing sodium-ion capacitors still have several technical shortcomings that urgently need to be addressed: First, sodium ions have a large ionic radius, resulting in slow insertion / extraction kinetics in traditional anode materials. This leads to poor reversible storage performance of sodium ions in electrode materials, limiting the rate performance of the devices. Second, the anode materials are prone to volume expansion during repeated sodium ion insertion and extraction, causing electrode structure collapse and damage, deteriorating interface stability, and significantly shortening the cycle life of the devices. Third, the energy storage mechanisms of the positive and negative electrodes of existing sodium-ion capacitors differ significantly, and the charge-discharge kinetics of battery-type anodes and capacitor-type cathodes are poorly matched, failing to fully utilize the performance of the positive and negative electrode materials and severely limiting the actual power output and overall performance of the devices.

[0005] In summary, there is an urgent need to develop a novel anode material that combines high capacity, fast sodium ion kinetics, and excellent structural stability within a suitable potential window, while also matching it with a suitable capacitive cathode and electrolyte system to achieve kinetic matching between the positive and negative electrodes and break through the performance bottleneck of existing sodium ion capacitors. Summary of the Invention

[0006] To address the shortcomings of existing sodium-ion capacitor anode materials, such as slow sodium ion insertion / extraction kinetics, severe volume expansion, poor structural stability, poor matching of positive and negative electrode kinetics, and limited overall performance, this invention aims to provide an in-situ electrochemical reconstruction method for rock salt phase NaTiO2 and its application in sodium-ion capacitors. This method achieves an in-situ phase transition from anatase phase TiO2 to highly stable rock salt phase NaTiO2 through an in-situ electrochemical reconstruction strategy, optimizing sodium ion transport channels, alleviating electrode volume deformation, and simultaneously achieving precise matching of positive and negative electrode kinetics when combined with a porous carbon cathode and a suitable electrolyte system. This synergistically improves the energy density, power density, and cycle stability of sodium-ion capacitors.

[0007] To achieve the above objectives, the present invention utilizes the following technical solution: an in-situ electrochemical reconstruction method for rock salt phase NaTiO2, comprising the following steps: S1. Preparation of anatase TiO2 nanomaterials; S2. Mix anatase TiO2 nanomaterials, conductive agent, binder and dispersant to prepare negative electrode slurry, coat the negative electrode slurry on the surface of current collector, dry and cut to obtain anatase TiO2 electrode; S3. Assemble a sodium-based half-cell using anatase TiO2 electrode as the working electrode and metallic sodium as the counter electrode, and inject sodium ion electrolyte. S4. The half-cell is electrochemically activated and the anatase phase TiO2 is irreversibly converted into the rock salt phase NaTiO2 anode through in-situ electrochemical reconstruction. S5. Prepare a porous carbon positive electrode sheet by assembling a rock salt phase NaTiO2 negative electrode, a porous carbon positive electrode, a separator, and a sodium ion electrolyte to obtain a sodium ion capacitor.

[0008] Preferably, in step S1, the anatase TiO2 nanomaterial can be prepared by hydrothermal method, liquid phase deposition method, or electrochemical deposition method, and its microstructure can be at least one of nanowires, nanorods, nanoribbons, nanosheets, nanoflowers, nanoparticles, hollow nanospheres, and thin films.

[0009] Preferably, in step S2, the conductive agent is selected from one or more of Ketjen black, conductive carbon black, acetylene black, carbon nanotubes, graphene, and highly crystalline graphite powder; the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, polyvinylidene fluoride, polyacrylonitrile, polyacrylic acid, polyoxyethylene, and sodium alginate; the dispersant is selected from one of water, N-methylpyrrolidone, ethanol, ethylene glycol, acetone, acetonitrile, propylene carbonate, N,N-dimethylformamide, and dimethyl sulfoxide; the current collector is selected from one of aluminum foil, copper foil, titanium foil, nickel foil, stainless steel mesh, nickel foam, graphite foil, carbon paper, and carbon cloth; and the mass ratio of anatase TiO2, conductive agent, and binder is 6:3:1 to 95:3:2.

[0010] Preferably, the solute of the sodium ion electrolyte in steps S3 and S5 is one of sodium hexafluorophosphate, sodium perchlorate, and sodium bis(trifluoromethanesulfonyl)imide, and the solvent is a single or mixed solvent of ether or ester; the electrolyte concentration is 0.01–10 mol / L.

[0011] Preferably, the electrochemical cyclic activation method in step S4 is selected from either cyclic voltammetry or constant current charge-discharge; when using cyclic voltammetry activation, the scan rate is 0.1–100 mV / s and the number of cycles is 3–200; when using constant current charge-discharge activation, the current density is 0.05–10 A / g and the number of cycles is 5–100.

[0012] Preferably, the porous carbon cathode preparation method in step S5 is as follows: porous carbon, conductive agent, and binder are added to a dispersant to mix and form a slurry, which is then coated onto a current collector and dried and cut; the graphene-based high-density porous carbon is selected from at least one of graphene, commercial activated carbon, biomass carbon, polymer-derived carbon, organic small molecule-derived carbon, graphyne, and carbon nanotubes.

[0013] Preferably, in step S5, the capacity ratio of the negative electrode to the positive electrode active material is N:P = 2:1 to 1:4; the sodium-ion capacitor device is any one of button type, sandwich type, soft-pack type, and planar interdigitated type.

[0014] Preferably, the rock salt phase NaTiO2 has a cubic rock salt crystal structure with continuous octahedral interstitial sodium ion diffusion channels inside the crystal, and 0.21 nm characteristic lattice fringes of the rock salt phase can be seen under a high-resolution transmission electron microscope.

[0015] Preferably, the sodium-ion capacitor prepared by the reconstruction method comprises a rock salt phase NaTiO2 negative electrode, a porous carbon positive electrode, and a sodium salt electrolyte.

[0016] Preferably, the sodium-ion capacitor is used in the fields of grid energy storage and industrial backup power.

[0017] The present invention has the following beneficial effects: 1. This invention achieves a controllable phase transition from anatase TiO2 to rock salt NaTiO2 through an in-situ electrochemical reconstruction strategy, optimizes the electrode microstructure, and significantly improves the sodium ion transport rate. It solves the industry pain points of slow sodium ion insertion / extraction kinetics, severe volume expansion, and poor structural stability of traditional titanium-based anodes, and significantly improves the rate performance and structural stability of the electrode.

[0018] 2. This invention adopts a precise matching design of positive and negative electrodes, combined with an appropriate electrolyte system, which completely solves the problems of mismatch between positive and negative electrode energy storage mechanisms and dynamic imbalance in traditional sodium-ion capacitors. It fully utilizes the performance of positive and negative electrode materials to achieve a synergistic improvement in device energy density and power density. The optimal energy density can reach 102Wh / kg, and the maximum power density can reach 6800W / kg.

[0019] 3. The precursor materials and carbon-based cathode materials used in this invention have mature preparation processes, readily available raw materials, and low costs. The electrode preparation process is highly compatible with existing mass production lines, requires no complex modification equipment, is suitable for large-scale industrial production, and has high industrialization value.

[0020] 4. The sodium-ion capacitor prepared by this invention has excellent stability and is suitable for various scenarios such as grid energy storage and industrial backup power supply, with a wide range of applications. Attached Figure Description

[0021] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments; Figure 1 This is a low-magnification scanning electron microscope image of the anatase phase TiO2 material of Example 1 of the present invention; Figure 2 This is a high-magnification scanning electron microscope image of the anatase phase TiO2 material in Example 1 of the present invention; Figure 3 This is a low-magnification transmission electron microscope image of the anatase phase TiO2 material in Example 1 of the present invention; Figure 4 This is a high-magnification transmission electron microscope image of the anatase phase TiO2 material in Example 1 of the present invention; Figure 5 The X-ray diffraction pattern of the anatase phase TiO2 material in Example 1 of this invention; Figure 6 The Raman spectrum of the anatase phase TiO2 material in Example 1 of this invention; Figure 7 The cyclic voltammetry curves for in-situ electrochemical activation of anatase phase TiO2 in Example 1 of this invention are shown. Figure 8 The X-ray diffraction patterns of different activation cycles in Example 1 of the present invention are shown. Figure 9 Examples of the present invention include Raman spectra under different activation cycles in Example 1. Figure 10 This is a high-resolution transmission electron microscope image of the rock salt phase NaTiO2 after in-situ reconstruction in Example 1 of the present invention; Figure 11 This is a selected area electron diffraction image of rock salt phase NaTiO2 after in-situ reconstruction in Example 1 of the present invention; Figure 12 The cyclic voltammetry curves of rock salt phase NaTiO2 after in-situ reconstruction in Example 1 of this invention are shown. Figure 13 The constant current charge-discharge curve of rock salt phase NaTiO2 after in-situ reconstruction in Example 1 of the present invention; Figure 14 This is the rate performance curve of rock salt phase NaTiO2 after in-situ reconstruction in Example 1 of the present invention; Figure 15 The cyclic voltammetry curves for the positive and negative electrode matching of the sodium ion hybrid supercapacitor in Example 1 of this invention are shown. Figure 16 The cyclic voltammetry curve of the sodium ion hybrid supercapacitor in Example 1 of this invention; Figure 17 The constant current charge-discharge curve of the sodium ion hybrid supercapacitor in Example 1 of this invention; Figure 18 The energy density and power density curves of the sodium ion hybrid supercapacitor in Example 1 of this invention are shown. Figure 19 This is a structural diagram of the in-situ phase transition substrate of the rock salt phase NaTiO2 of the present invention. Detailed Implementation

[0022] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.

[0023] This specific implementation adopts the following technical solution: an in-situ electrochemical reconstruction method for rock salt phase NaTiO2, including the following steps: Preparation of S1 anatase TiO2 nanomaterials Lithium acetate dihydrate was dissolved in a 1:1 mixture of N,N-dimethylformamide and glacial acetic acid. Tetrabutyl titanate was added under stirring. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure hydrothermal reactor and hydrothermally heated at 200 °C for 20 h. The reaction product was washed multiple times with ethanol and deionized water, dried overnight in a vacuum oven at 60 °C, and the dried powder was annealed in air at 350 °C for 2 h to obtain anatase TiO2 nanomaterials with an average diameter of about 10 nm and an interwoven network cluster structure.

[0024] In addition to hydrothermal methods, powders can also be prepared by liquid phase deposition or electrochemical deposition; the morphology of TiO2 can be replaced by nanorods, nanoribbons, nanosheets, hollow nanospheres, thin films, etc.

[0025] S2 Anatase TiO2 Electrode Preparation The above-mentioned anatase TiO2 powder, conductive agent, binder, and dispersant were mixed evenly to prepare a negative electrode slurry, which was divided into two systems: 1) Aqueous slurry: TiO2, Ketjen Black, CMC, SBR in a mass ratio of 8:1:0.5:0.5, with deionized water as the dispersant; 2) Oil-based slurry: TiO2, Super-P, PVDF in a mass ratio of 8:1:1, with NMP as a dispersant; The slurry was uniformly coated onto current collectors such as aluminum foil and titanium foil, and the active material loading was controlled at 1 mg / cm³. 2 After being thoroughly dried in a vacuum, it is cut into electrode sheets.

[0026] S3 Sodium-based half-cell assembly Select an ether-based or ester-based sodium salt electrolyte, preferably a 1 mol / L NaPF6in DEGDME ether electrolyte; use an anatase TiO2 electrode as the working electrode, a sodium metal sheet as the counter electrode, and glass fiber as the diaphragm to assemble a coin cell and inject electrolyte to seal it.

[0027] S4 In-situ electrochemical reconstruction for the preparation of rock salt phase NaTiO2 anode Electrochemical activation of the half-cell is provided, offering two activation processes: Process 1: Cyclic voltammetry, scan rate 1-2 mV / s, 3-200 cycles; the first CV curve shows an irreversible phase transition peak, and after 20 cycles the redox peaks are symmetrical and stable, and the anatase phase is completely transformed into the rock salt phase NaTiO2. Process 2: Constant current charge and discharge, current density 0.1 A / g, 5-100 cycles to complete crystal phase reconstruction.

[0028] After activation, the anatase phase characteristic peaks completely disappeared and the rock salt phase NaTiO2 characteristic diffraction peaks appeared. The rock salt phase characteristic lattice fringes of 0.21 nm were observed by XRD, Raman spectroscopy, high-resolution TEM and selected area electron diffraction.

[0029] S5 Sodium-ion Capacitor Preparation Graphene-based high-density porous carbon, Super-P, and PVDF were mixed in a mass ratio of 8:1:1, dispersed in NMP as a solvent, and uniformly coated onto an aluminum foil current collector, with the active material loading controlled at 2 mg / cm³. 2After vacuum drying, the positive electrode sheet is cut to obtain the positive electrode sheet; the carbon material can be replaced with commercial activated carbon, biomass carbon or carbon nanotubes, etc.; the positive electrode sheet prepared above is assembled and packaged with the rock salt phase NaTiO2 negative electrode, separator and sodium salt electrolyte obtained by in-situ reconstruction, and the capacity ratio of positive and negative electrode active materials is adjusted to N:P=1:1 to 1:2, and finally a button type, soft pack type or planar interdigitated sodium ion capacitor device is prepared.

[0030] The sodium-ion capacitor of this invention has the advantages of high energy density, ultra-high power density, long cycle life, low cost and high safety, and can be widely used in grid energy storage frequency regulation and peak shaving, new energy vehicle on-board energy storage systems, communication base stations and industrial equipment uninterrupted backup power supplies, portable high-power energy storage devices and other scenarios.

[0031] The characterization and testing methods used in all the following embodiments are as follows: 1) Scanning electron microscopy: Observe the microstructure of anatase TiO2.

[0032] 2) Transmission electron microscopy: Further observation of the microstructure of anatase TiO2.

[0033] 3) X-ray diffractometer: to test the X-ray diffraction pattern of anatase TiO2.

[0034] 4) Raman spectrometer: used to test the Raman spectrum of anatase TiO2.

[0035] 5) Electrochemical workstation: In-situ electrochemical activation, testing of the reconstructed rock salt phase NaTiO2 anode and sodium ion mixed supercapacitor cyclic voltammetry curves and constant current charge-discharge curves.

[0036] Example 1: This example provides an in-situ electrochemical reconstruction method for rock salt phase NaTiO2, including the following steps: S1. Preparation of anatase TiO2 nanomaterials: Lithium acetate dihydrate was dissolved in a 1:1 mixture of N,N-dimethylformamide and glacial acetic acid. Tetrabutyl titanate was added under stirring, and the mixture was transferred to a polytetrafluoroethylene-lined high-pressure hydrothermal reactor and hydrothermally heated at 200 °C for 20 h. The product was washed multiple times with ethanol and deionized water, dried overnight in a vacuum oven at 60 °C, and the dried powder was annealed in air at 350 °C for 2 h to obtain anatase TiO2 nanomaterials with an average diameter of about 10 nm and an interwoven network cluster structure.

[0037] S2. Anatase TiO2 powder was mixed with Ketjen Black (KJB), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a ratio of 8:1:0.5:0.5 and dispersed in deionized water. The slurry was then uniformly coated onto aluminum foil, and the loading of active material was controlled at 1 mg / cm³. 2The working electrode is obtained by drying in a vacuum oven and cutting.

[0038] S3. Select 1 mol / L NaPF6 in DEGDME ether electrolyte (NaPF6 salt has high dissociation degree, PF6⁻ anion has excellent electrochemical stability and is not easily decomposed at high potential; ether solvent DEGDME has low viscosity and moderate dielectric properties, can form a stable solvation structure with sodium ions, has high ionic conductivity and good temperature adaptability); use anatase TiO2 electrode as working electrode, sodium metal sheet as counter electrode, and glass fiber as separator to assemble a button-type sodium metal half cell and seal it.

[0039] S4. The half-cell was electrochemically activated using cyclic voltammetry at a scan rate of 1 mV / s for 20 cycles. An irreversible phase transition peak appeared in the first CV curve. After 20 cycles, the redox peaks were symmetrical and stable, indicating that the anatase phase had completely transformed into the rock salt phase NaTiO2. Characterization by XRD, Raman spectroscopy, high-resolution TEM, and selected area electron diffraction showed that the characteristic peaks of the anatase phase had completely disappeared, and the characteristic diffraction peaks of the rock salt phase NaTiO2 appeared. High-resolution electron microscopy observed 0.21 nm characteristic lattice fringes of the rock salt phase.

[0040] S5. Graphene-based high-density porous carbon, high-performance carbon black (Super-P), and polytetrafluoroethylene (PVDF) were mixed at a mass ratio of 8:1:1, and a positive electrode slurry was prepared using N-methylpyrrolidone (NMP) as a dispersant. The slurry was uniformly coated onto an aluminum foil current collector, and the active material loading was controlled at 2 mg / cm². After vacuum drying, the positive electrode sheet was cut to obtain a positive electrode sheet. The in-situ reconstructed rock salt phase NaTiO2 negative electrode and graphene-based high-density porous carbon positive electrode were combined with a glass fiber separator and 1 mol / L NaPF6 in DEGDME electrolyte for button-type encapsulation. The capacity ratio of the positive and negative electrode active materials was adjusted to N:P=1:2 to obtain a button-type sodium ion hybrid supercapacitor.

[0041] Test results: such as Figure 1 , Figure 2 As shown in the figure, the anatase TiO2 material prepared by the method described in this embodiment has a microstructure of one-dimensional nanowires with very uniform size. It can be clearly seen from the figure that the synthesized sample has a distinct coiled cluster structure. Figure 3 , Figure 4 By using a transmission electron microscope, we can further observe its morphological characteristics at high magnification. We can clearly see that the nanowires are distributed in a clustered and interwoven manner, and their slender nanowires can be observed at high resolution. Figure 5The X-ray diffraction pattern shows that the TiO2 nanowires exhibit characteristic diffraction peaks of the anatase phase. All diffraction peaks match the tetragonal anatase phase structure (lattice parameters a=b=4.5936 Å, c=2.9587 Å, space group I41 / amd), making them typical pseudocapacitive materials. Raman spectroscopy was also performed. Figure 6 ) at 144 cm -1 The Eg peak observed at [location] corresponds to the stretching vibration mode of the Ti-O bond, further verifying the anatase phase structure of the material. For example... Figure 7 The cyclic voltammetry curves for in-situ electrochemical activation are shown. In the first cycle, the anatase phase TiO2 reaches approximately 0.75 V (relative to Na). + Only a relatively broad oxidation peak appeared at / Na). After the first cycle, the CV curve underwent an irreversible change. After three cycles, the CV curve gradually showed obvious redox peak pairs and tended to be symmetrical. By the 20th cycle, the repeatability of the CV curve was good, indicating the formation of the ordered structure of the rock salt phase and the high reversibility of the sodium ion storage process. Figure 8 and Figure 9 X-ray diffraction and Raman spectroscopy tests were performed on the material during and after activation. It was observed that as the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase phase TiO2 gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Furthermore, Figure 10 and Figure 11 High-resolution transmission electron microscopy and selected area electron diffraction were performed on the material after activation, and lattice fringes and diffraction spots belonging to the rock salt phase were clearly visible. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method.

[0042] The rock-salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits excellent electrochemical performance, such as... Figure 12 As shown, the cyclic voltammetry curves at different scan rates all exhibited extremely symmetrical redox peaks, and in the constant current charge-discharge curves ( Figure 13 The curves also show a regular arrangement, and the charge-discharge behavior changes little with increasing current density. This indicates that the reconstructed material possesses stable electrochemical performance. Furthermore, its rate performance at different current densities was calculated based on the constant-current charge-discharge curves, such as... Figure 14 As shown, its capacitance did not fluctuate significantly with increasing current density, exhibiting good retention and indicating excellent rate performance. It was then assembled with graphene-based high-density porous carbon materials to obtain a sodium-ion hybrid supercapacitor. Based on the working characteristics and principles of the positive and negative electrode materials, voltage range matching was performed, such as... Figure 15 As shown. Based on the cyclic voltammetry curve of this sodium-ion hybrid supercapacitor ( Figure 16 ) and constant current charge-discharge curve ( Figure 17 It can be seen that the matched device exhibits extremely symmetrical electrochemical characteristics, and ion insertion / extraction can reach a relative equilibrium. Its energy density and power density can be calculated based on the galvanostatic charge-discharge curves. Figure 18 The energy density can reach 102 Wh / kg, and the power density can reach 6800 W / kg.

[0043] Example 2: The difference between this example and Example 1 is that electrochemical activation is replaced by constant current charge and discharge, 0.1 A / g for 10 cycles, and the other parameters remain unchanged.

[0044] The test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coil cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using constant current charge-discharge. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. Cyclic voltammetry curves at different scan rates all showed relatively symmetrical redox peaks, and the curves in the constant current charge-discharge curves also showed a regular arrangement. It was matched and assembled with graphene-based high-density porous carbon material to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 98 Wh / kg and the power density can reach 6300 W / kg.

[0045] Example 3: This example differs from Example 1 in that the CV scan rate is 2 mV / s, the cycle is 50 revolutions, and all other parameters remain unchanged. The test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. The cyclic voltammetry curves at different scan rates all show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was then matched and assembled with graphene-based high-density porous carbon materials to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 101Wh / kg, and the power density can reach 6500W / kg.

[0046] Example 4: This example differs from Example 1 in that the negative electrode uses an oil-based slurry with TiO2, Super-P, and PVDF in a ratio of 8:1:1, dispersed in NMP, while other parameters remain unchanged. The test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. The cyclic voltammetry curves at different scan rates all show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was then matched and assembled with graphene-based high-density porous carbon materials to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 89Wh / kg, and the power density can reach 5800W / kg.

[0047] Example 5: This example differs from Example 1 in that the negative electrode current collector is replaced with titanium foil, while all other parameters remain unchanged. The test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. The cyclic voltammetry curves at different scan rates all show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was then matched and assembled with graphene-based high-density porous carbon materials to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 100Wh / kg, and the power density can reach 6600 W / kg.

[0048] Example 6: This example differs from Example 1 in that the negative electrode binder is replaced with sodium alginate, and the ratio of TiO2, Ketjen Black, and sodium alginate is 8:1:1, while other parameters remain unchanged. The test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. The cyclic voltammetry curves at different scan rates all show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was then matched and assembled with graphene-based high-density porous carbon materials to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 92Wh / kg, and the power density can reach 5800W / kg.

[0049] Example 7: This example differs from Example 1 in that the negative electrode material ratio of TiO2, Ketjen Black, CMC, and SBR is 7:2:0.5:0.5, while other parameters remain unchanged. The device performance test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. The cyclic voltammetry curves at different scan rates all show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was then matched and assembled with graphene-based high-density porous carbon materials to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 84 Wh / kg, and the power density can reach 6400W / kg.

[0050] Example 8: This example differs from Example 1 in that the positive electrode active material loading is 1 mg / cm², the positive and negative electrode mass ratio N:P = 1:1, and all other parameters remain unchanged. The test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. The cyclic voltammetry curves at different scan rates all show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was then matched and assembled with graphene-based high-density porous carbon materials to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 84 Wh / kg, and the power density can reach 5200 W / kg.

[0051] Example 9: The difference between this example and Example 1 is that the electrolyte is replaced with a 1 mol / L NaPF6 in EC:DMC:DEC ester electrolyte, and the positive electrode is replaced with commercial activated carbon. In the electrolyte, the NaPF6 salt has a high degree of dissociation, and PF6... - Anions exhibit excellent electrochemical stability and are not easily decomposed at high potentials; ester solvents possess high dielectric constants and a wide antioxidant window, resulting in a more dense and stable SEI film; other parameters remain unchanged. The test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. The cyclic voltammetry curves at different scan rates all show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was matched and assembled with a graphene-based high-density porous carbon material cathode to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 74Wh / kg, and the power density can reach 4620W / kg.

[0052] Example 10: This example differs from Example 1 in that the positive electrode is replaced with commercially available activated carbon, while all other parameters remain unchanged. The device performance test results are as follows: The anatase TiO2 material prepared by the method described in this embodiment has a one-dimensional nanowire microstructure with very uniform size and obvious coiled cluster structure. In-situ electrochemical reconstruction was performed in a half-cell system using cyclic voltammetry. As the electrochemical process proceeded, the X-ray diffraction peaks and Raman characteristic peaks corresponding to the anatase TiO2 phase gradually disappeared, and characteristic peaks corresponding to rock salt appeared. Simultaneously, the material after activation exhibited lattice fringes and diffraction spots belonging to the rock salt phase. All the above test results indicate that the rock salt phase NaTiO2 electrode can be successfully prepared using the above-described in-situ electrochemical reconstruction method. The rock salt phase NaTiO2 electrode obtained by electrochemical reconstruction exhibits good electrochemical performance. Cyclic voltammetry curves at different scan rates show relatively symmetrical redox peaks, and the constant current charge-discharge curves also show a regular arrangement of curves. It was then matched and assembled with an activated carbon cathode to obtain a sodium-ion hybrid supercapacitor. The assembled device has relatively symmetrical electrochemical characteristics, and ion insertion / extraction can achieve a relative equilibrium. Its energy density and power density were tested and calculated, and the energy density can reach 78 Wh / kg and the power density can reach 4950 W / kg.

[0053] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. An in-situ electrochemical reconstruction method for rock salt phase NaTiO2, characterized in that, Includes the following steps: (S1) Preparation of anatase TiO2 nanomaterials; (S2) Mix anatase TiO2 nanomaterials, conductive agent, binder and dispersant to prepare negative electrode slurry, coat the negative electrode slurry on the surface of current collector, dry and cut to obtain anatase TiO2 electrode; (S3) Assemble a sodium-based half cell using an anatase TiO2 electrode as the working electrode and metallic sodium as the counter electrode, and inject sodium ion electrolyte. (S4) The half-cell is electrochemically activated and the anatase phase TiO2 is irreversibly converted into the rock salt phase NaTiO2 anode through in-situ electrochemical reconstruction. (S5) Prepare a porous carbon positive electrode sheet, and assemble a rock salt phase NaTiO2 negative electrode, a porous carbon positive electrode, a separator, and a sodium ion electrolyte to obtain a sodium ion capacitor.

2. The in-situ electrochemical reconstruction method for rock salt phase NaTiO2 according to claim 1, characterized in that, In step (S1), the anatase TiO2 powder can be prepared by hydrothermal method, liquid phase deposition method, or electrochemical deposition method, and its microstructure can be any one of nanowires, nanorods, nanoribbons, nanosheets, nanoflowers, nanoparticles, hollow nanospheres, or thin films.

3. The in-situ electrochemical reconstruction method for rock salt phase NaTiO2 according to claim 1, characterized in that, In step (S2), the conductive agent is selected from one or more of Ketjen black, conductive carbon black, acetylene black, carbon nanotubes, graphene, and highly crystalline graphite powder; the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, polyvinylidene fluoride, polyacrylonitrile, polyacrylic acid, polyethylene oxide, and sodium alginate; the dispersant is selected from one of water, N-methylpyrrolidone, ethanol, ethylene glycol, acetone, acetonitrile, propylene carbonate, N,N-dimethylformamide, and dimethyl sulfoxide; the current collector is selected from one of aluminum foil, copper foil, titanium foil, nickel foil, stainless steel mesh, nickel foam, graphite foil, carbon paper, and carbon cloth; the mass ratio of anatase TiO2, conductive agent, and binder is 6:3:1 to 95:3:

2.

4. The in-situ electrochemical reconstruction method for rock salt phase NaTiO2 according to claim 1, characterized in that, In steps (S3) and (S5), the solute of the sodium ion electrolyte is one of sodium hexafluorophosphate, sodium perchlorate, or sodium bis(trifluoromethanesulfonyl)imide, and the solvent is a single or mixed solvent of ether or ester; the electrolyte concentration is 0.01–10 mol / L.

5. The in-situ electrochemical reconstruction method for rock salt phase NaTiO2 according to claim 1, characterized in that, In step (S4), the electrochemical cyclic activation method is selected from either cyclic voltammetry or constant current charge-discharge; when using cyclic voltammetry activation, the scan rate is 0.1–100 mV / s and the number of cycles is 3–200; when using constant current charge-discharge activation, the current density is 0.05–10 A / g and the number of cycles is 5–100.

6. The in-situ electrochemical reconstruction method for rock salt phase NaTiO2 according to claim 1, characterized in that, The porous carbon cathode preparation method in step (S5) is as follows: porous carbon, conductive agent, binder are added to dispersant and mixed to form a slurry, which is then coated onto the current collector and dried and cut; the porous carbon is selected from at least one of graphene, commercial activated carbon, biomass carbon, polymer-derived carbon, organic small molecule-derived carbon, graphyne, and carbon nanotubes.

7. The in-situ electrochemical reconstruction method for rock salt phase NaTiO2 according to claim 1, characterized in that, In step (S5), the capacity ratio of the negative electrode to the positive electrode active material is N:P = 2:1 to 1:4; the sodium ion capacitor device can be any one of button type, sandwich type, soft-pack type, or planar interdigitated type.

8. The in-situ electrochemical reconstruction method for rock salt phase NaTiO2 according to claim 1, characterized in that, The NaTiO2 anode used in the aforementioned rock salt phase has a cubic rock salt crystal structure, with continuous octahedral interstitial sodium ion diffusion channels inside the crystal. Under high-resolution transmission electron microscopy, 0.21 nm characteristic lattice fringes of the rock salt phase can be seen.

9. A sodium-ion capacitor prepared by in-situ electrochemical reconstruction of rock salt phase NaTiO2, characterized in that, The sodium-ion capacitor prepared by the method of claim 1 comprises a rock salt phase NaTiO2 negative electrode, a porous carbon positive electrode, and a sodium salt electrolyte.

10. The application of the sodium-ion capacitor of claim 9 in the fields of grid energy storage and industrial backup power.